Infants' Prefrontal Hemodynamic Responses and Functional Connectivity During Joint Attention in an Interactive-Live Setting - Naoi, Nozomi; Minagawa, Yasuyo; Yamamoto, Jun-ichi; Kojima, Shozo (Frontiers in Medical Technology, 2022)
The present study examined cerebral hemodynamic responses and functional connectivity during joint attention either initiated by infants (Initiating Joint Attention, IJA condition) or by their partner (Responding to Joint Attention, RJA condition). To capture responses to natural social cues in infants aged 7–12 months using functional near-infrared spectroscopy (fNIRS), we employed an interactive-live paradigm for IJA and RJA. During the measurement, an adult sat facing an infant, and objects, such as small stuffed animals, paired with sound toys were presented to the right or left side of the screen. In the RJA condition, the adult gazed at the infants' eyes and then to the objects to encourage the infants to follow the adult's gaze. On the other hand, in the IJA condition, the adult followed the infant's gaze as it shifted to the presented object. Our results indicate that the concentration of oxy-Hb in the bilateral ventral prefrontal region had significantly decreased, then followed by an increase in the right dorsal prefrontal region in the RJA. In addition, a selective activation in the bilateral dorsal prefrontal region was seen in the IJA condition. Moreover, the infants exhibited increased functional connectivity especially within the right ventral prefrontal region during RJA condition when compared with IJA conditions. These findings suggest that RJA and IJA recruit specific brain networks localized in the prefrontal cortex of infants.